THE ROLE OF PHYSIOLOGY IN THE FORMATION OF GERONTOLOGY (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article analyzes the role of physiology in the formation of gerontology. The study addresses human aging processes, the functional characteristics of physiological systems, and their age-related changes. It demonstrates that theoretical and applied knowledge in physiology constitutes the principal scientific foundation for the development of gerontology, playing a crucial role in investigating aging processes, preventing disease, and formulating key recommendations aimed at increasing life expectancy. In addition, the article provides a scientific rationale for the role of physiological knowledge in gerontology in promoting a healthy lifestyle, proper nutrition, physical activity, and psychological stability.
Keywords: gerontology, physiology, aging process, healthy lifestyle, human health, body systems, life expectancy, physical activity, psychological stability.